Nové matrix metaloproteinázy v cyklickém endometriu - Pilka, R; Kudela, M; Hansson, S; Casslén, B (Ceska gynekologie, 2004)
OBJECTIVE: To examine the expression pattern of some novel matrix metalloproteinases (MMPs) in cycling endometrium. DESIGN: Experimental study. SETTING: Department of Obstetrics and Gynecology of the Palacky University Medical School and University Hospital, Olomouc, Czech Republic, Department of Obstetrics and Gynecology, University Hospital, Lund, Sweden. METHODS: We studied MMP-12, -16, -17, -19 and -26 mRNA in 39 normal endometrial samples obtained across the menstrual cycle. Based on histological examination, all specimens were classified according to an ideal 28 day menstrual cycle as early (n=8), mid (n=6) and late (n=7) proliferative phase, early (n=4), mid (n=4) and late (n=8) secretory phase and menstrual (n=3) phase. Cycle variation was examined in frozen samples using in situ hybridization. RESULTS: Three distinct pattern of MMP mRNA expression were detected in cycling endometrium. MMP-12 was expressed predominantly in perimenstrual period, MMP-16, -17 and 19 were expressed throughout the cycle and MMP-26 was found to be maximal in periovulatory period. CONCLUSION: Different endometrial expression patterns of novel MMPs during menstrual cycle may indicate their specific roles for menstruation, endometrial growth and remodelling and implantation.
Keywords: Endometrium; Humans; menstruační cyklus; Adult; matrixové metaloproteinasy; Matrix Metalloproteinases; dospělí; Middle Aged; hybridizace in situ; lidé středního věku; Menstrual Cycle; In Situ Hybridization; Female; endometrium; lidé; ženské pohlaví